2017
DOI: 10.1159/000479009
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Concentration and Its Association with Inflammatory Biomarkers in Spanish Schoolchildren

Abstract: Aim: To examine the correlation between inflammatory biomarkers and plasma β-carotene levels in children. Methods: A total of 564 Spanish schoolchildren aged 9-12 were observed and studied. Plasma β-carotene levels were assessed by HPLC. A β-carotene level <4.83 µg/dL (0.09 µmol/L) was considered deficient. Plasma tumour necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were measured by immunoenzyme assays. Serum high-sensitivity C-reactive protein (hs-CRP) was tested by immunonephelometry. Results: Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…An adapted physical activity daily questionnaire [22] [see Additional File 2], which has been previously used in other studies [23][24][25], was filled out by the parents about their children. Questions find the time spent during weekdays and weekends in different kind of physical activities (including active play and extracurricular sport classes, physical education and daily life activities) and sedentary behaviors (including watching TV, playing videogames, tablet or computer use).…”
Section: Physical Activity Datamentioning
confidence: 99%
“…An adapted physical activity daily questionnaire [22] [see Additional File 2], which has been previously used in other studies [23][24][25], was filled out by the parents about their children. Questions find the time spent during weekdays and weekends in different kind of physical activities (including active play and extracurricular sport classes, physical education and daily life activities) and sedentary behaviors (including watching TV, playing videogames, tablet or computer use).…”
Section: Physical Activity Datamentioning
confidence: 99%
“…Additionally, by administrating β-carotene- 14 C intraduodenally, Crain et al reported that appreciable amounts of β-carotene was converted to ATRA in the rat intestinal mucosa ( 15 ), highlighting the possibility that both β-carotene and ATRA could be bioactive compounds that affected the homeostasis of the gastrointestinal (GI) system. Another study showed that subjects containing lower levels of β-carotene had increased levels of CRP and interleukin-6 (IL-6) ( 16 ), an inflammatory cytokine that contributes to the pathogenesis of various GI diseases ( 17 , 18 ). Furthermore, multiple mechanistic studies were conducted to explore the signaling pathways involved in the anti-inflammatory activity of β-carotene.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive secondary metabolites produced during biotransformation stimulate pro-fibrogenic cytokines, inflammatory markers and collagen synthesis during the development of hepatic fibrosis (Ezhilarasan, 2018). It has been reported that inflammatory status, in particular IL-6 levels, appears to be negatively associated with plasma beta-carotene levels (Rodríguez-Rodríguez et al, 2017). IL-1α, IL-1β, TNF-α are the cytokines which are pro-inflammatory and production of these and activation of immune cells which are inherent are typical features of inflammation.…”
Section: Discussionmentioning
confidence: 99%